2004
DOI: 10.1897/03-584.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting maternal body burdens of organochlorine pesticides from eggs and evidence of maternal transfer in Alligator mississippiensis

Abstract: Few data exist regarding maternal-embryonal transfer of organochlorine pesticides (OCPs) in reptiles. The objective of the present study was to evaluate maternal transfer of OCPs in American alligators (Alligator mississippiensis) from low-, intermediate-, and high-OCP-exposure sites. Overall, total OCP burdens ranged from less than 0.8 ppb in blood to more than 44,000 ppb in abdominal adipose tissue (wet wt concentrations). Lipid-adjusted ratios of maternal adipose burdens (total OCPs) to yolk burdens were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 27 publications
2
42
1
1
Order By: Relevance
“…Prior studies by our laboratory (conducted between 1999 and 2002) have indicated vastly different levels of OCP exposure and early-life-stage mortality across these sites. Lake Lochloosa was selected as the reference site because of its low level of OCPs (overall mean for total OCPs in yolk of 231630 mg/kg) and high clutch viability, defined as the number of live hatchlings/number of eggs in the clutch (71626%) (Rauschenberger et al, 2004). Lake Griffin was selected as an intermediate OCP-exposure site because yolk concentrations average 4,4146617 mg/kg, and Lake Apopka and Emeralda were selected as high OCP-exposure sites because yolk concentrations average 15,91161,786 mg/kg and 15,23861,787 mg/kg, respectively (Rauschenberger et al, 2004).…”
Section: Sites and Animal Collectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies by our laboratory (conducted between 1999 and 2002) have indicated vastly different levels of OCP exposure and early-life-stage mortality across these sites. Lake Lochloosa was selected as the reference site because of its low level of OCPs (overall mean for total OCPs in yolk of 231630 mg/kg) and high clutch viability, defined as the number of live hatchlings/number of eggs in the clutch (71626%) (Rauschenberger et al, 2004). Lake Griffin was selected as an intermediate OCP-exposure site because yolk concentrations average 4,4146617 mg/kg, and Lake Apopka and Emeralda were selected as high OCP-exposure sites because yolk concentrations average 15,91161,786 mg/kg and 15,23861,787 mg/kg, respectively (Rauschenberger et al, 2004).…”
Section: Sites and Animal Collectionsmentioning
confidence: 99%
“…Lake Lochloosa was selected as the reference site because of its low level of OCPs (overall mean for total OCPs in yolk of 231630 mg/kg) and high clutch viability, defined as the number of live hatchlings/number of eggs in the clutch (71626%) (Rauschenberger et al, 2004). Lake Griffin was selected as an intermediate OCP-exposure site because yolk concentrations average 4,4146617 mg/kg, and Lake Apopka and Emeralda were selected as high OCP-exposure sites because yolk concentrations average 15,91161,786 mg/kg and 15,23861,787 mg/kg, respectively (Rauschenberger et al, 2004). In addition, clutch success on Lakes Apopka and Griffin and on Emeralda are below those observed at the reference Lochloosa site (51631% , 44633%, and 52635%, respectively) (Rauschenberger et al, 2004).…”
Section: Sites and Animal Collectionsmentioning
confidence: 99%
See 3 more Smart Citations